Integration of Islamic Law Principles in Overcoming Failure: Mediate Family Cases in The North Sulawesi Religious Court - Harun, Nurlaila; Yusuf, Nasruddin; Fernando, Henky; Larasati, Yuniar Galuh (El-Usrah: Jurnal Hukum Keluarga, 2026)
This study examines the failure of mediation in family cases at the North Sulawesi Religious Court and emphasizes the importance of integrating Islamic legal principles to address these issues. Although many studies have addressed mediation failures, this study offers a more in-depth perspective by highlighting how the dominance of legal formalities often ignores the substance of peaceful dispute resolution. Through a qualitative approach, in-depth interviews are conducted with judges, mediators, and parties involved in the mediation process. Thematic analysis is then used to identify patterns and themes from the collected data. The study results show that one of the leading causes of mediation failure is the lack of application of Islamic legal principles, such as the activeness of mediator judges in promoting peace. In addition, local wisdom ('urf) that is supposed to strengthen mediation is often overlooked, which reduces the effectiveness of the mediation process. The success of mediation, if it occurs, is more often determined by external pressures, such as family pressures, than by the mediation itself. Therefore, this study emphasizes the need for stronger integration between Islamic legal principles and mediation approaches in Religious Courts to achieve fairer, more peaceful dispute resolution for all parties.